In the era of endo-venous ablation of varicose veins, is surgery still competitive? - Elmallah, Ahmed S.; Alkhateeb, Yehia M.; Elmallah, Said I. (International Surgery Journal, 2018)
Background: There are different evolving minimally invasive surgical options for varicose veins (VV) treatment. This study compared Endo-venous Laser Ablation (EVLA) and foam sclerotherapy Vs high tie and multiple phlebectomy / ligation without vein stripping. Methods: 185 lower limbs with primary VV and sapheno-femoral junction (SFJ)incompetence were included. Patients were divided into two groups. Group A: 85 limbs in 78 patients (4 had chronic venous ulcers) were treated by EVLA & foam sclerotherapy under tumescent anesthesia. Group B: 100 limbs in 100 patients (5 had chronic venous ulcers) were treated by high tie and multiple phlebectomy/ ligation under local anesthesia. All patients had duplex ultrasound preoperative and 4 weeks and 1 year postoperatively. Postoperative outpatient follow-up was 4 weeks, 3, 6 and 12 months. Results: All procedures were successful. Early postoperative recurrence in 3 limbs (3.52%) in EVLA and no early recurrence in group B. Patients with venous ulcers healed within 3-5 weeks in both groups. Postoperative pigmentation was higher in group B. Mean time of procedure was 60-90 min and 60-150 min respectively. Significant pain in first week was more in group A (40 patients) than group B (22 patients) p<0.05. No DVT, wound infection, permanent nerve affection nor skin burn was recorded in both groups. Return to normal activities was quicker in Group B compared to group A but mean cost per limb was higher in Group B (1000 -1500 US $) versus Group A (500-750 US$). Conclusions: Both procedures are effective and safe in treating varicose veins. Minimally invasive surgery was less costly, more postoperative pain and was associated with longer operative time. EVLA was associated with more postoperative pigmentation and 1 year VV recurrence.